Role Of Intraoperative Imprint Cytology And Frozen Section In The Diagnosis Of Breast Lumps - Ara Begum, Kazi Nishat; Huq, Fahmida; Haque, Md Nazmul; Hossain, Maliha; Akond, Abdul Khaleque; Siddiqui, Md Ashiqur Rahman (Journal of Chittagong Medical College Teachers' Association, 2014)
The present cross-sectional study was conducted in the Department of Pathology, Dhaka Medical College Hospital, Dhaka over a period 12 months to evaluate the usefulness of intra-operative imprint cytology in diagnosing various breast lesions and to compare its diagnostic accuracy with those of frozen and paraffin sections. A total of 101 cases of breast tumours, diagnosed clinically or mamographically, who underwent elective surgery were consecutively included in the study. The mean age of the patients was 37.7 – 14.5 years. The sensitivity and specificity of imprint cytology in differentiating breast carcinoma from those who did not have breast carcinoma were 91% and 94.1% respectively. The positive and negative predictive values (PPVs and NPVs) of the test were 96.8% and 84.2% respectively. The percentages of false positive and false negative were 3.2% and 15.8% respectively. The overall diagnostic accuracy of imprint cytology was 92%. The sensitivity of frozen sections in correctly diagnosing carcinoma of breast was 95.5%, while the specificity of the test in ruling out those who did not have carcinoma was 97.1%. The positive and negative predictive values of the test were 98.5% and 91.7% respectively. The percentages of false positive and false negative were 1.5% and 8.3% respectively. The overall diagnostic accuracy of the test was 96%. The overall diagnostic accuracy of the two procedures is almost comparable. However, the imprint cytology has merit over frozen section in that it can be done quickly and thus helps operating surgeons to decide about margin clearance. JCMCTA 2013 ; 24 (2): 4-8